Astrocode: a serious game for the development of computational thinking skills - Bione, Javier (2017)
Serious Games have been the focus of different research works in last years, as a consequence of their possibilities for educational scenarios. These games are used for purposes other than mere entertainment, but they are still motivating and attractive to users. More recent research works have also emphasized the potential of serious games for learning, skill acquisition, and attitude and behavior changes considering that they allow learners to experience situations that are impossible in the real world and provide engaging activities which are stimulating, generate strong emotions, require complex information processing, and provide challenges. On the other hand, programming teaching is a growing area that is spreading beyond computer science courses of studies. Computational Thinking (CT) is related to a problem solving process that involves a number of characteristics and skills such as applying abstraction and algorithms design. CT is important in computer applications, but it can also be used to support problem solving across all disciplines. Today, there is a growing corpus of experiences whose goals include CT skills development. This paper presents AstroCode, a serious game which is oriented to introduce players to CT skills such as algorithm design using variables and control structures. The description of the game and the test sessions held with different students of the National University of La Plata are detailed in this article. The first results show student engagement and motivation using these types of games in an educational scenario, as well as the difficulties they face in the use of control structures and how AstroCode helps students apply them.